Energy efficiency analysis of channel aware geographic-informed forwarding (CAGIF) for wireless sensor networks - Zhang, Lili (2011)
This letter analytically examines the achievable energy efficiency of channel aware geographic-informed forwarding (CAGIF) algorithm, which chooses the next hop relay node by taking into consideration the underlying channel conditions, rather than purely maximizing the forwarding progress. The theoretical analysis in terms of the average forward distance is developed and the upper bound and lower bound of the average energy consumption are provided by referring to the retransmission techniques. Numerical results show that CAGIF significantly improves the energy efficiency over the previous geographic information based routing algorithms that ignore the channel conditions.